Establishing a Soldier Wireless Sensor Network (WSN) Communication for Military Operation Monitoring - Mohd Nazri Ismail; Mohd ‘Afizi Shukran; Mohd Rizal Mohd Isa; Mohd Adib; Omar Zakaria (Institute of Advanced Engineering and Science, 2018)
The study investigates and develops components for implementing an effective and efficient military knowledge/information/communication in closed network architecture. Since military personnel are always on the move, the dissemination of knowledge/information/communication needs a mobile platform to accommodate mobility of people. The mobile and wireless network platform should be able to sustain the remoteness and seclusion of military operation areas. Communication is one of key problems of a military operation especially due to environmental constraints. This study proposes on establishing a future soldier communication device with mobile wireless sensor network (WSN) and mobile network to suit the infantry operations in the jungle. The operational areas are considered to restricted and challenging locations. Wireless sensor network (WSN) will become inexpensive and common over the next decade Thus, a thorough study is vital to develop the most suitable smart equipment and network requirements for Malaysia’s military eco-system. Finally, this study has successfully developed new smart device prototype using WSN approach for Military operation. In addition, this prototype can be used for Search and Rescue (SAR) operation. This prototype is able to transmit death and location status, movement location status, health monitoring and status to the base station.